Fundamentals of nuclear pharmacy - Saha, Gopal B (Springer, 2013)
Upon publication of the First Edition, Fundamentals of Nuclear Pharmacy has emerged as the standard text reference in nuclear medicine. Generously supplemented with charts, tables, and more than 100 illustrations, the new Fifth Edition of this classic text has been thoroughly updated by judiciously replacing obsolete sections with new, cutting-edge material. Each chapter provides the reader with well-delineated descriptions of the subject matter, from the basic atomic structure to the clinical uses of radiopharmaceuticals. Previous editions were highly acclaimed for their clarity and accuracy; Dr. Saha set new standards for making complex theoretical concepts readily understandable for students and practitioners in nuclear pharmacy and nuclear medicine.